Endovascular Therapy vs. Thrombolysis in Pre-stroke Dependent Patients With Large Vessel Occlusions Within the Anterior Circulation - Kastrup, Andreas; Roth, Christian; Politi, Maria; Alexandrou, Maria; Hildebrandt, Helmut; Schröter, Andreas; Papanagiotou, Panagiotis (Frontiers in Neurology, 2021)
Background: In the past few years, several randomized trials have clearly shown that endovascular treatment (ET) in addition to intravenous thrombolysis (IVT) is superior to IVT alone in patients with proximal cerebral arterial occlusions. However, the effectiveness of ET in pre-stroke dependent patients (modified Rankin Scale ≥3) is uncertain. Methods: Using our prospectively obtained stroke database, we analyzed the impact of pre-stroke dependence on the rates of poor outcome (discharge mRS 5–6), in-hospital death, infarct sizes, and symptomatic intracranial hemorrhage (SICH) in patients with distal intracranial carotid artery M1 and M2 occlusions during two time periods. Results: From 1/2008 to 10/2012, a total of 544 patients (455 without and 89 with dependence) were treated with IVT, and from 11/2012 to 12/2019 a total of 1,061 patients (919 without and 142 with dependence) received ET (with or without IVT). Irrespective of the treatment modality, the dependent patients had significantly higher rates of poor outcome (55 vs. 32%, p < 0.001), death (24 vs. 11%; p < 0.001), or SICH (8.2 vs. 3.6%, p < 0.01) than independent patients. In dependent patients, ET significantly reduced the rates of poor outcome (49 vs. 64%, p < 0.01) and led to smaller infarcts, whereas the rates of in-hospital death (25 vs. 22%; p = 0.6) or SICH (8.5 vs. 7.9%, p = 0.9) were comparable between both treatment modalities. Conclusions: Compared with IVT, ET avoids poor outcome and leads to smaller infarcts in dependent patients. However, the overall high rates of poor outcome in this patient population stress the importance to perform decisions based on a case-by-case basis.